Rare mimicker of transient ischaemic attacks: the syndrome of transient headache and neurological deficits with cerebrospinal luid lymphocytosis - Hazeena, Philo; Vanukuri, Naga Karthik; V., Shankar (International Journal of Research in Medical Sciences, 2019)
The syndrome of transient headache and neurologic deficits associated with cerebrospinal fluid lymphocytosis (HaNDL) is a benign and self limiting disorder characterized by 1 or more episodes of severe headache and transient neurologic deficits with lymphocytic pleocytosis in the cerebrospinal fluid. We report a case of a 30-year-old male who presented with four episodes of headache followed by hemi paresis and hemisensory loss in a week the patient was completely asymptomatic in between each episode of headache with neurological deficits. Persistent serial imaging to visualize the brain were normal with evidence of cerebrospinal fluid lymphocytosis, which lead to the diagnosis of HaNDL. We need to advocate a high degree of suspicion for HaNDL in the background of strong clinical history and findings, when imaging is normal.